Exploring the impact of seasonal variations on the chemical composition, antinociceptive, and anti-inflammatory properties of Pogostemon heyneanus Benth. essential oil - Santos, Paulo Vinicius Lima; Jerônimo, Lucas Botelho; Ribeiro, Weyda Suyane Campos; Lopes, Gustavo Moraes; Leão Neto, João Henrique de Castro; da Silva, Hugo Borges Oliveira; da Silva, Pedro Iuri C.; Silva, Renata Cunha; da Silva, Joyce Kelly; Freitas, Jofre Jacob S.; Mourão, Rosa Helena V.; Setzer, William N.; et al. (Frontiers in Pharmacology, 2024)
The essential oil chemical composition of a Pogostemon heyneanus specimen was monthly monitored from October 2021 to July 2022 to evaluate the climatic influences on its yield and chemical composition. The leaves, collected monthly over a ten-month period, were submitted to hydrodistillation. The oils obtained were analyzed by gas chromatography coupled to a mass spectrometer and gas chromatography coupled to flame ionization detector. The Pogostemon heyneanus essential oil (PhEO) was tested in vivo to evaluate its peripheral analgesic actions through the abdominal writhing test induced by acetic acid, and peripheral analgesia by tail immersion. Neurogenic and inflammatory pain were evaluated by formalin test, and acute oral toxicity of the oil was also verified. PhEO presented 27 chemical constituents with the highest predominance of patchoulol (43.6-76.9%), α-bulnesene (0.2-12.7%), α-guaiene (0.4-8.9%), seychellene (3.8-5.1 %) and pogostol (0.0-8.2%). The climatic parameters insolation, humidity, rainfall, and temperature did not influence the essential oil yield or the main chemical constituents, except for pogostol, which presented a strong (r = 0.73) and statistically significant (p < 0.05) correlation with temperature. PhEO did not display toxicity at the maximum 300 mg/kg dosage. The oil showed low peripheral and central analgesic action at 100 mg/kg, while in the neurogenic and inflammatory pain inhibition tests, no actions related to PhEO were observed. In the carrageenan-induced peritonitis test, PhEO did not reduce the migration of leukocytes to the peritoneal cavity compared to the control group. P. heyneanus is a resistant plant to seasonal influences and a source of patchoulol. Despite ethnopharmacological indications, no in-vivo biological activities such as neurogenic or inflammatory pain were identified in the present work. So, the low influence of the climatic parameters on chemical composition can infer that the low pharmacological activity is also not subject to climatic variations, that is, it does not change due to the climate.